Evaluation of heat transfer coefficient between polymer and cavity wall for improving cooling and crystallinity results in injection molding simulation. (5th April 2015) - Liu, Yao; Gehde, Michael
Abstract: Heat transfer coefficient (HTC), as a parameter that describes the thermal transfer ability of the interface between the polymer melt and the metallic wall, has a dominant role in calculating temperature distribution. This research focuses on evaluating the HTC between the polymer and the cavity wall for improving the cooling and crystallinity simulation. A mathematical model for evaluating HTC was presented. Injection molding experiments were carried out to obtain temperature data near the cavity wall; HTC was calculated after data processing. Injection molding simulation was performed with different values of HTC, which represented various processing conditions. Finally, relative crystallinity from the simulation were obtained and compared with the result acquired by differential scanning calorimetry analysis. This research showed that HTC significantly influences the simulation of cooling rate and crystallinity. Comprehension of heat conduction phenomenon across the interface can promote the accuracy of injection molding simulation to predict mechanical behavior and dimensional precision. Highlights: We present a mathematic model for evaluating HTC during injection molding. HTC under different processing and surface condition was obtained through experiment. Variation mechanism of HTC is investigated based on experimental result. Observed HTC can improve simulation precision of cooling rate and crystallinity. Observed HTC can represent various surface conditions in injection molding simulation.